Pengaruh Terapi Rendam Air Hangat terhadap Penurunan Derajat Edema Pasien Gagal Ginjal Kronik Post Hemodialisis Rumah Sakit Harapan Bunda Jakarta - Dytya Amalia Romadhan; Rizki Destiana; Mila Sartika; Cicilia Nony Ayuningsih (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Chronic kidney disease (CKD) is a degenerative condition characterized by progressive and irreversible decline in renal function. This condition leads to fluid imbalance, often resulting in edema, particularly in the lower extremities. Edema negatively affects muscle strength and mobility due to the increased diffusion distance of oxygen and nutrients from capillaries to tissues. Common clinical manifestations among CKD patients include shortness of breath, dizziness, fatigue, nausea, vomiting, restlessness, excessive thirst, and difficulty urinating (Nurbadriyah, 2021). One non-pharmacological intervention that can be applied to reduce edema is warm water immersion therapy, which works by improving blood circulation and promoting interstitial fluid removal. This study aimed to determine the effect of warm water immersion therapy on reducing the degree of edema in chronic kidney disease patients after hemodialysis. The research employed a quasi-experimental design with a one-group pretest–posttest approach. Data were analyzed using the Wilcoxon test. The results showed that 18 respondents (72%) experienced a decrease in the degree of edema after receiving warm water immersion therapy, with a p-value of 0.000 (< 0.05), indicating a statistically significant effect between pre- and post-intervention measurements. These findings indicate that warm water immersion therapy is an effective non-pharmacological intervention for reducing the degree of edema in post-hemodialysis CKD patients. Regular implementation of this therapy is recommended as a supportive self-care measure to help control fluid balance and enhance patient comfort and quality of life.